2020
DOI: 10.1039/d0py00280a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface charge on the formulation of elongated PEG-b-PDLLA nanoparticles

Abstract: Amphiphilic PEG-PDLLA copolymers undergo assembly into polymersomes and can be transformed into tubular shapes using dialysis. By fine-tuning the shape change conditions also amine- and carboxylic acid modified polymersomes can now be effectively turned into tubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…To engineer various nanoparticle morphologies, we synthesized a range of well-defined block copolymers comprising PEG, PTMC, PCL, and PDLLA in various combinations, using procedures presented in our previous reports (Figures S1–S5). To enable further study into the impact of surface chemistry upon performance, copolymers with PEG-terminal amine (A) and carboxylic acid (CA) moieties were also prepared and blended with unmodified (U) polymers for assembly into A- and CA-bearing particles. Spherical and tubular polymersomes were fabricated using our protocols where 10 wt % of A or CA groups could be stably incorporated, yielding particles with sizes around 450 (U/A) or 250 nm (CA) (Figures S6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To engineer various nanoparticle morphologies, we synthesized a range of well-defined block copolymers comprising PEG, PTMC, PCL, and PDLLA in various combinations, using procedures presented in our previous reports (Figures S1–S5). To enable further study into the impact of surface chemistry upon performance, copolymers with PEG-terminal amine (A) and carboxylic acid (CA) moieties were also prepared and blended with unmodified (U) polymers for assembly into A- and CA-bearing particles. Spherical and tubular polymersomes were fabricated using our protocols where 10 wt % of A or CA groups could be stably incorporated, yielding particles with sizes around 450 (U/A) or 250 nm (CA) (Figures S6).…”
Section: Resultsmentioning
confidence: 99%
“…Polymer synthesis and particle fabrication were conducted as previously described. , Reaction schemes and polymer characterization data can be found in Figures S1–4. Fluorescent polymers were prepared by conjugation with Bodipy-FL-CO 2 H dye via esterification (Figure S5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that the salt concentrations used to induce the final shapetransformed morphology depended on both the charge of the polymer and the salt concentration. 38 Similarly, Che et al observed that, by attaching an azide functionality to the PEG side in PEG-b-PS diblocks, the vesicles underwent shape transformation from spherical to stomatocytes and eventually hexagonally packed hollow hoops when they were dialyzed against NaCl solutions. 39 The final morphologies were determined by the concentration of the NaCl solution used during the dialysis.…”
Section: Osmotic Pressure and Concentration Gradientsmentioning
confidence: 95%
“…86 In addition to hydrophobic interactions, electrostatic interactions are also developed to construct polymeric hybrid vesicles with NPs in the wall. 87 Wan and co-workers constructed electro-responsive vesicles by employing the Surface chemistry also plays an essential role in controlling the localization of NPs in vesicle walls. As reported by Mai and Eisenberg, the NPs can be tunably incorporated into only the central parts of the vesicle walls.…”
Section: Particles In Vesiclementioning
confidence: 99%